Today's woman in world religions - Sharma, Arvind 1940- (McGill studies in the history of religions, 1994)
This book examines how the women's movement is affecting traditional religions and civilizations throughout the world. It reviews cases of global impact in Hinduism, Buddhism, Taoism, Confucianism, Judaism, Christianity, Islam, and Australian aboriginal religion. This volume completes the trilogy devoted to women in world religions, edited by Arvind Sharma. The second book in the series is entitled Religion and Women. The present work surveys the position of women in the religious traditions covered in the first volume of the trilogy, Women in World Religions, placing these traditions in contemporary context.